Makna Simbolik yang Berwujud Materil dan Non Materil dalam Tradisi Karia pada Masyarakat Muna - Sitti Hermina (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
Karia tradition is regarded as the most important ceremony for girls in Muna when entering adulthood. In the implementation of this Karia tradition has many symbols in it that implies. However, the phenomenon is happening now, most people in Muna especially young women do not know the meaning contained in the Karia tradition. Therefore, this study aims to answer two problems, namely stages in Karia tradition and symbolic meaning tangible material and non-material in stages Karia tradition in society Muna. This research uses qualitative descriptive method. Data collected by participant observation, in-depth interviews with key informants and informant principal as well as through the documents related with the tradition of Karia. Data were analyzed descriptively qualitative comprising data reduction, data presentation and conclusion. The results showed that the stages in the process of Karia tradition in Muna society consists of three stages, namely, the preparation phase, the implementation phase, and the final stage. In the preparation phase, the committee has been formed to prepare all needs, including oe kaalano sokaghombo, kaalano bhansano bhea. During the implementation phase, there are several processions, namely: kafoluku, kaghombo, kabhansule, kabhalengka, kabhindu, kafosampu, katandano wite, tarilinda, kabasano dhoa Salama, and kahapui and final stage tradi tion carried kafolantono Karia bhansa / kaghorono bhansa in the river. The symbols contained in Karia procession is divided into two, namely the form of material and non-material form. Meaning contained in the tradition of Karia both tangible material and non-material is purifying oneself for women and as one of the media in educating women associated with domestic life, community and country. Keywords: meaning, symbol, karia tradition in society Muna